Theoretical Reflections on the Emergence of Global Labor Solidarity. Issue 2 (June 2014) - Scipes, Kim
<x xml:space="preserve">Abstract</x> This article recognizes that there is no theory of global labor solidarity and tries to lay some groundwork specifically toward developing such. It begins with an examination of "labor imperialism, " which has recently been theoretically grounded, and rejects that. It then discusses previous efforts to theoretically develop the concept of "new labor internationalism, " particularly highlighting the thinking of Peter Waterman. It joins this with Kim Scipes' three levels of labor internationalism. Following, it replaces the concept of international labor solidarity with global labor solidarity so as to recognize new developments by workers in multiple sites around the globe: workers around the world are no longer waiting for "Northern" labor movements' resources or even ideas, but are trying to build real labor solidarity across the globe, acting in solidarity with their brothers and sisters from across the world.